2018
DOI: 10.3390/cryst8040145
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and Langmuir Behavior of the Cage Occupancy in the Nitrogen Gas Hydrate

Abstract: Abstract:Clathrate hydrates are ice-like systems in which nanometric water cages encapsulate guest molecules. Functionalizing clathrate hydrates is an important issue, accomplished by playing with their chemical composition and their cage structure. In this issue, the cage occupancy and its kinetics constitute key information for future developments. In many aspects, nitrogen gas hydrate represents an interesting system not only for its applied relevance (e.g., gas separation and methane/carbon dioxide exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…14,15 Experimentally, it has been shown that the LCs in both hydrates have the ability to catch and release guest molecules as the pressure and the temperature vary. 13,15,20 Together with previous DFT calculations performed on carbon monoxide hydrate, 14,39 the present investigation clearly underlines that the cage occupancy is the factor driving the stability, i.e. leading to the lower potential energy of the formed hydrate structure.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…14,15 Experimentally, it has been shown that the LCs in both hydrates have the ability to catch and release guest molecules as the pressure and the temperature vary. 13,15,20 Together with previous DFT calculations performed on carbon monoxide hydrate, 14,39 the present investigation clearly underlines that the cage occupancy is the factor driving the stability, i.e. leading to the lower potential energy of the formed hydrate structure.…”
Section: Discussionsupporting
confidence: 80%
“…As reported from time-dependent neutron diffraction analysis, 13 nitrogen hydrate forms in the sI clathrate metastable structure and transforms into the thermodynamically stable sII clathrate structure for which the cage occupancy plays a role. 20 Such structural metastability involves different potential energies for the sI and sII structures. The nitrogen hydrate stability has been analyzed in terms of DFT-calculated potential energies by following the methodology detailed in the work of Petuya et al 39 The potential energy considered for the present analysis corresponds to intermolecular energies whose reference states are defined on the basis of the intramolecular energies of the isolated molecular species (water and nitrogen).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Worthwhile to mention is, that pure clathrates of CO and N 2 are first formed in the sI-structure and they transform, in time, to the thermodynamically stable phase sII. [22][23][24][25] In the case of the mixed CO-N 2 hydrates 26 , this structural change promotes the CO molecular selectivity 17 . In this paper, this property is documented for the first time by combining Grand Canonical Monte Carlo (GCMC) simulations and Raman Scattering experiments.…”
Section: Introductionmentioning
confidence: 99%